Pola Interaksi Masyarakat Bangsawan dengan Non Bangsawan di Desa Sakra Kabupaten Lombok Timur - Srianti, Srianti (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2018)
This study aims to determine the patterns of interaction, customs, language and behavior of nobles and non-nobles in Sakra village. The research method used in this study is the phenomenology method. Data collection by observation, interviews, and documentation. The data collected in this study is data about the patterns of interaction of the Sakra Village community. The results of this study indicate that in Sakra Village there are two distinct groups of social identities known as aristocrats (perwangse) and non-aristocrats (jajarkarang). As for this group of perwangse, there are those who are native nobles and immigrant nobles. These two different social groups have different identities both in language, customs, marriage system, social status and others. The perwangse group has a higher social status than jajar coral, and of course its identity is also different. But over time because several factors such as education, economics, and social status of the high nobility experienced a shift and a kind of cultural erosion. So it can be concluded that the nobility in Sakra Village was once the most influential social group, but because of several declining status factors or in short there has been a cultural shift and kinship system in the Sakra Village community.